Evaluating the Sources of Graphenes Resistivity Using Differential Conductance - R. Somphonsane; H. Ramamoorthy; G. He; J. Nathawat; C.-P. Kwan; N. Arabchigavkani; Y.-H. Lee; J. Fransson; J. P. Bird (My University, 2017)
We explore the contributions to the electrical resistance of monolayer and bilayer graphene, revealing transitions between different regimes of charge carrier scattering. In monolayer graphene at low densities, a nonmonotonic variation of the resistance is observed as a function of temperature. Such behaviour is consistent with the influence of scattering from screened Coulomb impurities. At higher densities, the resistance instead varies in a manner consistent with the influence of scattering from acoustic and optical phonons. The crossover from phonon-, to charged-impurity, limited conduction occurs once the concentration of gate-induced carriers is reduced below that of the residual carriers. In bilayer graphene, the resistance exhibits a monotonic decrease with increasing temperature for all densities, with the importance of short-range impurity scattering resulting in a "universal" density-independent (scaled) conductivity at high densities. At lower densities, the conductivity deviates from this universal curve, pointing to the importance of thermal activation of carriers out of charge puddles. These various assignments, in both systems, are made possible by an approach of "differential-conductance mapping", which allows us to suppress quantum corrections to reveal the underlying mechanisms governing the resistivity.
Keywords: Bilayer graphene; Charge carrier; Phonon scattering; Carrier scattering; Graphene research and applications